Kocha, lubi, miłuje... (to loves, to likes, to cherishs). Words related to love in Polish language at present and in the past - Broszko, Małgorzata (Migracja w języku, literaturze i kulturze, 2020)
The article is about words that have a related meaning and these derivatives which have changed meaning to various degrees. In some cases lexicalization has occurred. The semantic of these words is associated with the feeling of love in contemporary Polish or it was associated with love several centuries ago. These words have as roots: • -lub-: lubić (to like), luby (darling), lubieżny (salacious); • -koch-: kochać (to love), kochanek (a lover), rozkosz (a delight); • -mił-: miłować (to cherish), miłość (a love), miły (nice), miłosierdzie (mercy).The article is a historical and semantic analysis of these words and is attempting to find the reasons and the effect of semantic changes in those words.